2021
DOI: 10.1161/circinterventions.121.010641
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Aorta in Transcatheter Self-Expanding Valves: Insights From the HORSE International Multicentre Registry

Abstract: Background: An increased degree of aortic angulation (AA) represents a challenging feature for bioprosthesis positioning. Whether AA has an impact on procedural outcomes of contemporary self-expanding valves remains unsettled. The aim of this study was to evaluate the impact of AA on procedural outcomes of transcatheter aortic valve replacement with contemporary self-expanding valves. Methods: The HORSE (Horizontal Aorta in Transcatheter Self-Expanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Similarly, the HORSE registry showed that TAVI in patients with an AA more than 49 • was associated with worst outcomes. However, among these cases, patients treated with ACURATE Neo valve showed more favourable outcomes in comparison with these cases treated with the EVOLUTE R/PRO THV [46].…”
Section: Patients With Horizontal Aortamentioning
confidence: 85%
“…Similarly, the HORSE registry showed that TAVI in patients with an AA more than 49 • was associated with worst outcomes. However, among these cases, patients treated with ACURATE Neo valve showed more favourable outcomes in comparison with these cases treated with the EVOLUTE R/PRO THV [46].…”
Section: Patients With Horizontal Aortamentioning
confidence: 85%
“…The HORSE registry is an international registry in which patients undergoing transfemoral TAVI using self-expandable valves were retrospectively enrolled across sixteen European centers between September 2014 and April 2020 [10]. All patients provided informed consent to participate in the registry and agreed to the use of their data for scientific purposes.…”
Section: Methodsmentioning
confidence: 99%
“…The HORSE registry is an international registry in which patients undergoing transfemoral TAVI using self-expandable valves were retrospectively enrolled across sixteen European centers between September 2014 and April 2020 [10]. All patients provided informed consent to participate in the registry and agreed with the use of their data for scientific purposes.…”
Section: Methodsmentioning
confidence: 99%